A Combined Proteomic and Metabolomic Strategy for Allergens Characterization in Natural and Fermented Brassica napus Bee Pollen - Shuting Yin; Shuting Yin; Yuxiao Tao; Yusuo Jiang; Lifeng Meng; Liuwei Zhao; Xiaofeng Xue; Qiangqiang Li; Liming Wu (Frontiers in Nutrition, 2022)
Bee pollen is consumed for its nutritional and pharmacological benefits, but it also contains hazardous allergens which have not been identified. Here, we identified two potential allergens, glutaredoxin and oleosin-B2, in Brassica napus bee pollen using mass spectrometry-based proteomics analyses, and used bioinformatics to predict their antigenic epitopes. Comparison of fermented (by Saccharomyces cerevisiae) and unfermented bee pollen samples indicated that glutaredoxin and oleosin-B2 contents were significantly decreased following fermentation, while the contents of their major constituent oligopeptides and amino acids were significantly increased based on metabolomics analyses. Immunoblot analysis indicated that the IgE-binding affinity with extracted bee pollen proteins was also significantly decreased after fermentation, suggesting a reduction in the allergenicity of fermented bee pollen. Furthermore, fermentation apparently promoted the biosynthesis of L-valine, L-isoleucine, L-tryptophan, and L-phenylalanine, as well as their precursors or intermediates. Thus, fermentation could potentially alleviate allergenicity, while also positively affecting nutritional properties of B. napus bee pollen. Our findings might provide a scientific foundation for improving the safety of bee pollen products to facilitate its wider application.